Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1093/infdis/jiu147
|View full text |Cite
|
Sign up to set email alerts
|

Biological Differences Between the Sexes and Susceptibility to Tuberculosis

Abstract: Globally, far more men than women have tuberculosis. Although the cause of this bias is uncertain, epidemiological factors have historically been considered the driving force. Here, we discuss evidence that biological differences between the sexes may also be important and can affect susceptibility to mycobacterial infection. We discuss the possible underlying mechanisms, with particular focus on how sex hormones modulate the immune responses necessary for resistance to tuberculosis. Studying these differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
163
2
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(205 citation statements)
references
References 47 publications
17
163
2
7
Order By: Relevance
“…In our analysis we found a weak association between male gender and higher IFN-g levels at baseline in the long term retrospective (LTR) analysis. This could be linked to sex hormones causing differences in genderassociated immune responsiveness, specifically those of IFN-g [10,23]. Our results are consistent with previous studies that show women have significantly lower IFN-g response after PPD stimulation than men (after adjustment for age, BMI and M.tb infection) [13] as well as less strong tuberculin skin testing results [24].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In our analysis we found a weak association between male gender and higher IFN-g levels at baseline in the long term retrospective (LTR) analysis. This could be linked to sex hormones causing differences in genderassociated immune responsiveness, specifically those of IFN-g [10,23]. Our results are consistent with previous studies that show women have significantly lower IFN-g response after PPD stimulation than men (after adjustment for age, BMI and M.tb infection) [13] as well as less strong tuberculin skin testing results [24].…”
Section: Discussionsupporting
confidence: 91%
“…Differences in TB disease notification rates between the genders have been well documented and are thought to be a result of both social and biological factors [10]. In our analysis we found a weak association between male gender and higher IFN-g levels at baseline in the long term retrospective (LTR) analysis.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…A strong sex bias is observed for many autoimmune diseases(2), which are much more common in females, including autoimmune thyroid diseases, systemic sclerosis, systemic lupus erythematosus. Furthermore, the incidence and severity of several microbial infections, including malaria and tuberculosis(3), influenza(4), hepatitis(5) and HIV-1(6) are different between the sexes(7). In HIV-1 infection, clinical studies have shown faster disease progression and stronger immune activation in females compared to males for the same level of viral replication, as well as better control of initial viremia in women during primary infection.…”
Section: Introductionmentioning
confidence: 99%
“…Females exhibit more-robust immune responses to antigenic challenges, like infection and vaccination, in comparison to that in males. Given the fact that immune cells express specific receptors for CRP C-reactive protein, CSF cerebrospinal fluid, ESR Erythrocyte sedimentation rate Note: Statistically significant P-values are depicted in italics sex hormones and are responsive to changes in hormone levels, this gender variation might be explained by the modulatory effect of female sex hormones on the immune response towards Mycobacterium tuberculosis associated antigens [17,18]. Patients with disseminated or extrapulmonary disease are considered to have higher bacillary/antigen loads, with a relative immunodeficient response, resulting in an increased risk of both paradoxical reactions and IRIS.…”
Section: Discussionmentioning
confidence: 99%